Mitigating Phytophthora in rubber - Roy, C. Bindu (Indian Horticulture, 2019)
Rubber tree (Hevea brasiliensis), being the source of raw material for over 50,000 industrial products, is one of the most important non-food crops. The Amazon tropical rain forest region is the centre of origin of Para rubber tree and the crop is harvested in the form of latex. Rubber tree is cultivated in many countries around the world predominantly in south and south-east Asia. The world production of natural rubber exceeds five million tonnes and is still increasing with the smallholder farmers producing a major share.